2021
DOI: 10.5194/essd-2021-418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep-Learning-Based Harmonization and Super-Resolution of Near-Surface Air Temperature from CMIP6 Models (1850–2100)

Abstract: Abstract. Future global temperature change would have significant effects on society and ecosystems. Earth system models (ESM) are the primary tools to explore the future climate change. However, ESMs still exist great uncertainty and often run at a coarse spatial resolution (The majority of ESMs at about 2 degree). Accurate temperature data at high spatial resolution are needed to improve our understanding of the temperature variation and for many applications. We innovatively apply the deep-learning(DL) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Table 1 unequivocally highlights the superiority of DPDM in downscaling results compared to other statistical methods. This includes deterministic models such as Enhanced Deep Residual Networks for Super-Resolution with Generative Adversarial framework (EDSR-GAN), known for their superiority over traditional statistical techniques [40][41][42][43] , as well as the widely-used linear interpolation methods (Lerp) in meteorology 44,45 (PSNR), Structure Similarity Index Measure (SSIM), and Root Mean Square Error (RMSE). It is worth mentioning that this superiority is particularly evident in the case of precipitation and temperature downscaling, which are very important for social life in a warming climate.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 unequivocally highlights the superiority of DPDM in downscaling results compared to other statistical methods. This includes deterministic models such as Enhanced Deep Residual Networks for Super-Resolution with Generative Adversarial framework (EDSR-GAN), known for their superiority over traditional statistical techniques [40][41][42][43] , as well as the widely-used linear interpolation methods (Lerp) in meteorology 44,45 (PSNR), Structure Similarity Index Measure (SSIM), and Root Mean Square Error (RMSE). It is worth mentioning that this superiority is particularly evident in the case of precipitation and temperature downscaling, which are very important for social life in a warming climate.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that deep learning can reproduce data in pattern coupling with excellent performance (Sun and Archibald,. 2021;Wei et al, 2021). In this study, considering temporal variation, the application of neural network and machine learning reproduce dataset with higher ability of projecting climatological rainfall and temperature under SSP1-2.6, SSP2-4.5 and SSP5-8.5.…”
Section: Higher Credibility Of the Proposed Ensemble Dataset By Compa...mentioning
confidence: 93%
“…(3) development of machine learning (ML) with nonlinear function to train selected models adjusted by bias correction (Xu et al, 2020;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation